Menuju Reforma Agraria dan Perhutanan Sosial di Banyuwangi, Jawa Timur : (Sebuah Telaah Spasial dan Tematik) - Tiara Nur Khanifa; Syarli Syanurisma; Ahmad Nashih Luthfi (Sekolah Tinggi Pertanahan Nasional, 2021)
ABSTRACT This research is an effort to resolve the conflicts of forest tenurial (PPTKH) which is carried out with a spatial approach and thematic to provide recommendations for Agrarian Reform and Social Forestry (RAPS) policies. The spatial approach is carried out by satellite images processing with a 20-year period, which are taken in 2019 and 1999. The thematic approach is carried out by conducting the Identification of Land Tenure, Ownership, Utilization and Use. The results of the identification in the location of tenurial forest by the community with utilizing the SPOT 7 imagery for 2019, there are the 120,40 hectares area of Kedungasri Village that have been occupied by the community but claimed as Perum Perhutani forest area. The thematic study also confirms that land tenure has been carried out since the Japanese period. Of the 120.40 hectares area, there are 50.80 hectares or about 42% was directed towards agrarian reform policies through by Forest Area Swap (TMKH). The location that will be proposed for RAPS have land uses in the form of agriculture and settlements. At the provincial level, this study also found that the forest area in East Java is more than 30% of the total area of the province. The possibility of agrarian reform policies in Java is very open. It is not appropriate if Java has been exempted from agrarian reform policies. Keywords : PPTKH, RAPS, Spatial Approach, IP4T, 30% forest area INTISARI Penelitian ini sebagai upaya Penyelesaian Penguasaan Tanah Kawasan Hutan (PPTKH) yang dilakukan dengan pendekatan spasial dan tematik untuk memberikan rekomendasi kebijakan Reforma Agraria dan Perhutanan Sosial (RAPS). Pendekatan spasial dilakukan dengan cara melakukan pengolahan citra satelit dengan tempo 20 tahun, yaitu citra satelit yang diambil pada tahun 2019 dan tahun 1999. Pendekatan tematik dilakukan dengan cara melakukan Identifikasi Penguasaan, Pemilikan, Pemanfaatan dan Penggunaan Tanah (IP4T). Hasil identifikasi lokasi penguasaan tanah kawasan hutan oleh masyarakat dengan memanfaatkan citra SPOT 7 tahun 2019 yaitu di wilayah Desa Kedungasri terdapat penguasaan tanah kawasan hutan oleh masyarakat namun diklaim sebagai kawasan hutan Perum Perhutani seluas 120,40 ha. Dari telaah tematik juga memperkuat bahwa penguasaan tanah telah dilakukan sejak masa Jepang. Dari luasan 120,40 ha tersebut, seluas 50,80 ha atau sekitar 42% diarahkan untuk kebijakan reforma agraria melalui Tukar Menukar Kawasan Hutan (TMKH). Pada level propinsi, penelitian ini juga menemukan bahwa luas kawasan hutan di Jawa Timur lebih dari 30% dari total luas propinsi sehingga terbuka besar kemungkinan kebijakan reforma agraria di Jawa yang selama ini mendapatkan pengecualian. Kata kunci : PPTKH, RAPS, Pendekatan Spasial, IP4T, 30% kawasan hutan